Russian Federation : Environmental Policy in the Transition Years - Sporek, Tadeusz (Federacja Rosyjska : polityka ochrony środowiska w okresie przejściowym, 2010)
The transformation of Russian Federation and in environmental policy in the transition years had a great influence on Russian economy and politics. This article presents processes that took place in Russian Federation customs policy and consolidation of Russian democratization and liberalization. The period has been characterized by increasing attention to state environmental protection during the 1990, a devolution toward regional environmental protection into Putin's "strengthening of vertical power".
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 167-180
Keywords: Russian Federation; environmental policy; protection; liberalization; democratization